2018
DOI: 10.3892/mco.2018.1576
|View full text |Cite
|
Sign up to set email alerts
|

Primary Castleman's disease in the liver: A case report and literature review

Abstract: Abstract. Castleman's disease (CD) is a lymphoproliferative abnormality, also referred to as giant lymph node hyperplasia or follicular lymphoid hyperplasia. The occurrence of CD in the liver is rare. Radiological diagnosis of hepatic CD by computed tomography (CT) and magnetic resonance imaging (MRI) remains difficult. On imaging, hepatic CD is often expressed as a single, well-defined soft tissue lesion, with rare cystic degeneration and focal necrosis. The CD lesions appear as hypervascular with abundant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…CD has been diagnosed within variable primary sites, including the mediastinal, intra-abdominal, cervical, axillary, retroperitoneal or inguinal lymph nodes [ 7 , 15 ]. Rarely, UCD presents in unusual sites, such as the lungs, orbits, mouth, tonsil, nasopharynx, liver and small intestine [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Single-site involvement of renal parenchyma is extremely rare in this disease, with only a little relevant literature published.…”
Section: Discussionmentioning
confidence: 99%
“…CD has been diagnosed within variable primary sites, including the mediastinal, intra-abdominal, cervical, axillary, retroperitoneal or inguinal lymph nodes [ 7 , 15 ]. Rarely, UCD presents in unusual sites, such as the lungs, orbits, mouth, tonsil, nasopharynx, liver and small intestine [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Single-site involvement of renal parenchyma is extremely rare in this disease, with only a little relevant literature published.…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors had high mitotic activity, areas of necrosis, and vascular invasion and expressed at least one neuroendocrine marker (chromogranin, synaptophysin, or CD56)[ 14 , 15 ]. The Ki-67 proliferation index was very high (> 80%)[ 16 , 17 ]. Immunohistochemical staining of four cases of pure LCNEC, three cases of LCNEC associated with endometrioid carcinoma, and one case of small cell neuroendocrine carcinoma associated with endometrioid carcinoma demonstrated abnormalities of mismatch repair protein expression[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in the 1950s by pathologist Benjamin Castleman when he identified localised mediastinal lymph node enlargement that was histologically different from the thymoma he suspected 2. Through emerging research over the past 70 years, CD has been found to comprise at least four disorders that have characteristic histopathological features, but variable aetiology, presentation, treatment and prognosis 3. CD is broadly classified in terms of its location, unicentric or multicentric nature and its histological features.…”
Section: Introductionmentioning
confidence: 99%
“…Unicentric disease involves a single enlarged lymph node or lymph node region, whereas multicentric disease involves several lymph node stations 3. Histologically, Castleman first discovered the hyaline vascular subtype, characterised by lymphoid follicles with germinal centre regression or involution and hypervascular capillary proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation